2008
DOI: 10.1007/s11096-008-9257-9
|View full text |Cite
|
Sign up to set email alerts
|

Consumer satisfaction with opioid treatment services at community pharmacies in Australia

Abstract: Community pharmacies providing opioid substitution treatment in New South Wales appear to be providing a level of service that is satisfactory to the clients of those services. However, many participants were concerned about a lack of privacy, the high cost of treatment, and being treated differently to other customers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…34 In another study investigating consumer perspectives, researchers , observed that in general consumers expressed high levels of satisfaction with OST services in pharmacies in NSW, but that there was less satisfaction with the quality of privacy afforded them, and the fact that OST patients claimed to be made to wait longer than other patients or clients in the pharmacy, perceiving they were "treated differently". 35 Interestingly, 23% of the participants in this study were in debt to the pharmacy for their dispensing fees. 35 Dispensing fees have been identified as an important barrier for patients accessing community pharmacy-based OST.…”
Section: Provision Of Opioid Substitution Therapy Services In Australmentioning
confidence: 82%
“…34 In another study investigating consumer perspectives, researchers , observed that in general consumers expressed high levels of satisfaction with OST services in pharmacies in NSW, but that there was less satisfaction with the quality of privacy afforded them, and the fact that OST patients claimed to be made to wait longer than other patients or clients in the pharmacy, perceiving they were "treated differently". 35 Interestingly, 23% of the participants in this study were in debt to the pharmacy for their dispensing fees. 35 Dispensing fees have been identified as an important barrier for patients accessing community pharmacy-based OST.…”
Section: Provision Of Opioid Substitution Therapy Services In Australmentioning
confidence: 82%
“…There is no set dispensing fee charged to OST patients and there are large price disparities across community pharmacies in the various Australian jurisdictions [12]. Previous research indicated that OST fees ranged between $18 and $56 per week [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Although financial support towards dispensing fees is only one aspect to encourage patients to be treated and be retained in care financial instability is one concern that is frequently raised [10,18,19]. The demographic of patients on OST is generally in the lower income bracket and it was estimated in 2005 that only 17% of Australian OST patients received their main income from paid work [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations